Dark sacred night [compact disc, unabridged] : a Ballard and Bosch novel - Connelly, Michael, 1956- (Hachette Audio, 2018)
Teaming up with Harry Bosch to reopen a cold case, LAPD detective Renée Ballard navigates interpersonal differences to pursue justice for a murdered runaway in Hollywood.